2006
DOI: 10.1096/fj.05-4863fje
|View full text |Cite
|
Sign up to set email alerts
|

Purified human hematopoietic stem cells contribute to the generation of cardiomyocytes through cell fusion

Abstract: To obtain insights into the cardiomyogenic potential of hematopoietic tissue, we intravenously (i.v.) injected purified hematopoietic stem/progenitor cells into newborn recipients that may fully potentiate the developmental plasticity of stem cells. Transplantation of mouse bone marrow (BM) lineage antigen-negative (Lin-) cells resulted in the generation of the cells that displayed cardiomyocyte-specific antigenic profiles and contractile function when transplanted into syngeneic newborn recipients. To clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 36 publications
(46 reference statements)
0
49
0
Order By: Relevance
“…Further, multiple studies found no evidence of bone marrow MSCs or NSC fusion with hepatocytes, pancreatic endocrine cells, endothelial cells or epidermis. [107][108][109][110] While high levels of specific cytokines can induce fusion of MSCs with cardiomyocytes or striated muscle cells, 111,112 it appears that nonembryonic stem cells have little capacity to fuse with cells of a recipient organism. Possibly, fetal or adult stem or progenitor cells will have more utility than embryonic stem cells as delivery vehicles.…”
Section: Toxicity/tumorigenicitymentioning
confidence: 99%
“…Further, multiple studies found no evidence of bone marrow MSCs or NSC fusion with hepatocytes, pancreatic endocrine cells, endothelial cells or epidermis. [107][108][109][110] While high levels of specific cytokines can induce fusion of MSCs with cardiomyocytes or striated muscle cells, 111,112 it appears that nonembryonic stem cells have little capacity to fuse with cells of a recipient organism. Possibly, fetal or adult stem or progenitor cells will have more utility than embryonic stem cells as delivery vehicles.…”
Section: Toxicity/tumorigenicitymentioning
confidence: 99%
“…11 In these mice, extremely high human cell engraftment rates and increases in well-differentiated human multilineage hematopoietic cells from human hematopoietic stem cells (HSCs), as compared with parent immunodeficient mice, were observed. [17][18][19] Humanized mice that retain various human immune cells are often termed human immune system mice 3 or human hematolymphoid system mice. 20 The production of humanized mice that are reconstructed with human cells would facilitate analysis of the underlying mechanisms of human disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The GFP(1)Iba1(2) cells observed in the corneal stroma under a fluorescent microscope may represent such cells. On the other hand, it is reported that BM hematopoietic stem cells give rise to cardiomyocytes through cell fusion, not transdifferentiation (Ishikawa et al, 2006). We cannot exclude the possibility that BM-derived GFP(1) cells may fuse with resident corneal keratocytes.…”
Section: Discussionmentioning
confidence: 81%
“…Nonpurified BM cells harvested from femurs and tibiae of GFP transgenic mice at 8-12 weeks of age, were intravenously injected into wild-type C57BL/6 mice (N 5 6) within 48 hr of birth after 400 cGy irradiation, as previously described (Hisatomi et al, 2003;Ishikawa et al, 2006). The GFP transgenic mice were C57BL/6 mice that transgenically express eGFP driven by the chicken beta actin promoter (Okabe et al, 1997;Ikawa et al, 1998) and purchased from Jackson Laboratory (Bar Harbor, ME).…”
Section: Materials and Methods Animals And Bm Syngeneic Transplantationmentioning
confidence: 99%